Repeated variate stress increased voiding frequency and altered TrpV1 and TrpV4 transcript expression in lower urinary tract (LUT) pathways in female mice - Sidwell, Amanda B.; McClintock, Celia; Beča, Katharine I.; Campbell, Susan E.; Girard, Beatrice M.; Vizzard, Margaret A. (Frontiers in Urology, 2023)
Psychological stress is associated with urinary bladder dysfunction (e.g., increased voiding frequency, urgency and pelvic pain); however, the mechanisms underlying the effects of stress on urinary bladder function are unknown. Transient receptor potential (TRP) channels (vanilloid family) may be potential targets for intervention due to their distribution in the LUT and role in pain. Here, we examine a model of repeated variate stress (RVS) of 2 week (wk) or 4 wk duration in female mice and its effects on bladder function, anxiety-like behavior, and TRPV transcript expression in urinary bladder and lumbosacral spinal cord and associated dorsal root ganglia (DRG). Using continuous infusion, open-outlet cystometry in conscious mice, RVS significantly (p ≤ 0.05) decreased infused volume and intermicturition interval. Bladder pressures (threshold, average, minimum, and maximum pressures) were unchanged with RVS. Quantitative PCR demonstrated significant (p ≤ 0.05) changes in TrpV1 and TrpV4 mRNA expression between control and RVS cohorts in the urothelium, lumbosacral spinal cord, and DRG. Future directions will examine the contribution of TRP channels on bladder function, somatic sensation and anxiety-like behavior following RVS.